The Position of State Institutions (Main & Supporting) Against the Trias Politica Concept Based on the Indonesian State Administration System - Muhammad Hoiru Nail (Focus Journal : Law Review, 2021)
State institutions in a country listed in its constitution are a reflection that the country exists to provide certainty that the country is present for its citizens. State institutions themselves in a constitution consist of at least 2 (two) namely the main state organs (main state organs) and state auxiliary bodies (state auxiliary body), but in the 1945 Constitution of the Republic of Indonesia this is not explicitly stated. The two state institutions have a very important role in the Indonesian state administration system. the existence of the trias politica concept affecting the position of state institutions guaranteed in the 1945 Constitution of the Republic of Indonesia, requires a complete and comprehensive understanding of the study of the powers of state institutions guaranteed in a constitution. The flow of changes to the 1945 Constitution of the Republic of Indonesia only on the pretext of the need or importance of existing state institutions and has not been explicitly stated in the 1945 Constitution of the Republic of Indonesia must be dammed considering the sacredness of the 1945 Constitution of the Republic of Indonesia must be maintained (it is not easy to change the 1945 Constitution of the Republic of Indonesia)